Plant Parasitic Nematodes and their management in crop production: a review - Mandal, Honey Raj; Katel, Shambhu; Subedi, Sudeep; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Plant Parasitic Nematodes are small worm like transparent, bilateral symmetry, pseudocoelomate, multicellular, free living or parasitic microorganism which are predatory, aquatic, terrestrial, entopathogenic, ectoparasite, endoparasite, semi-endoparasite or sedentary. They cause substantial problems to major crops throughout the world, including vegetables, fruits, and grain crops. The root knot and cyst nematodes are economically important pests in numerous crops. Crop damage from nematodes is not readily apparent in most cases, and it often remains hidden by the many other factors limiting plant growth. In the past, the control of the nematodes has been based on the synthetic nematicides, the number of which has been drastically restricted in the EU because of their environmental side effects and subsequent restriction in European Union (EU) rules and regulations. Many other methods like cultural control, biological control, use of biotechnological tools and methods, use of resistant cultivars are tested and proven successful in controlling different species of nematodes all over the world. Alternatively, combinations of the different methods are proven to be highly effective both economically and environmentally.